2007
DOI: 10.1016/j.marpolbul.2006.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Mercury contamination in invertebrate biota in a temperate coastal lagoon (Ria de Aveiro, Portugal)

Abstract: Effect of anthracene and solar ultraviolet radiation exposure on gill ATPase and selected hematological measurements in bluegill sunfish (Lepomis macrochirus). Aquatic Toxicology 24, 207-218.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
4
16
1
Order By: Relevance
“…This study showed that total mercury concentrations in S. plana and H. diversicolor correlate well with total mercury levels in sediments, which is in accordance with other works (Coelho et al, 2007;Žižek et al, 2007). On the other hand, the bivalve S. plana Table 1 Physico-chemical characterization of the sediments and mercury content of S. plana and H. diversicolor in the field conditions for the three sampling sites.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed that total mercury concentrations in S. plana and H. diversicolor correlate well with total mercury levels in sediments, which is in accordance with other works (Coelho et al, 2007;Žižek et al, 2007). On the other hand, the bivalve S. plana Table 1 Physico-chemical characterization of the sediments and mercury content of S. plana and H. diversicolor in the field conditions for the three sampling sites.…”
Section: Discussionsupporting
confidence: 90%
“…In the case of S. plana, this bivalve exceeded the maximum mercury levels allowed for human consumption (0.5 lg g À1 wet weight, Regulation EC 466/ 2001). This species reached higher mercury concentrations than the polychaete H. diversicolor, which may be due in part to its longer life span (Coelho et al, 2007) (Table 1).…”
Section: Mercury Bioaccumulation Ratesmentioning
confidence: 99%
“…Total tissue Hg concentrations in T. tubifex were comparable with values reported for benthic invertebrates inhabiting reference and Hg-contaminated field sites and may be considered environmentally realistic (Coelho et al 2007;Rizzo et al 2011). Genetic resistance to inorganic Hg has been reported for this species, which may be related to detoxification and storage (by way of metallothionein-like proteins or metal-rich granules) or to accumulation and subsequent loss of metal through autotomy of caudal segments (Klerks and Bartholomew 1990;Horne 2003a, 2003b).…”
Section: Discussionsupporting
confidence: 71%
“…Methylmercury is more toxic, bioavailable and prone to bioaccumulation and biomagnification in estuarine food webs, ultimately finding its way to species usually consumed by humans (Wang et al, 1998;Clarkson et al, 2003;Tchounwou et al, 2003). Despite methylmercury typically being below 1% of total mercury in sediments, levels in fish are commonly above 90%, due to a higher biomagnification of the organic form (Lawson and Mason, 1998;Coelho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In contaminated areas, this will imply a decisive role in mercury mobilization and transfer from sediments and detritus to higher levels in the food chain, considering that this species is the main dietary item for several estuarine predators (Scaps, 2002). Some information on mercury accumulation by this species is available in literature (Muhaya et al, 1997;Coelho et al, 2007), where it was found to accumulate less mercury than Scrobicularia plana despite similar dietary strategies (Coelho et al, 2007). Nevertheless, mercury levels were not corrected for individual age and hence no direct comparison between the two species can be made.…”
Section: Introductionmentioning
confidence: 99%